Production and efficiency of large wildland fire suppression effort: A stochastic frontier analysis - Katuwal, Hari; Calkin, David E.; Hand, Michael S. (Journal of environmental management, 2016)
This study examines the production and efficiency of wildland fire suppression effort. We estimate the effectiveness of suppression resource inputs to produce controlled fire lines that contain large wildland fires using stochastic frontier analysis. Determinants of inefficiency are identified and the effects of these determinants on the daily production of controlled fire line are examined. Results indicate that the use of bulldozers and fire engines increase the production of controlled fire line, while firefighter crews do not tend to contribute to controlled fire line production. Production of controlled fire line is more efficient if it occurs along natural or built breaks, such as rivers and roads, and within areas previously burned by wildfires. However, results also indicate that productivity and efficiency of the controlled fire line are sensitive to weather, landscape and fire characteristics. •We examine production and efficiency of wildland fire suppression effort.•Determinants of efficiency are examined using stochastic frontier analysis.•Production of fire line is more efficient if constructed along natural breaks.•Productivity of controlled line is sensitive to weather and fire characteristics.